Being More Psychologically Healthy: The Concept of Mental Health According to Zakiah Daradjat and its Application in Islamic Educational Institutions - Achmad Syahid (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2016)
This study presents the thought and the role of Prof. Zakiah Daradjat, a modern female Muslim leader with multitalents in Indonesia. She is an expert in psychology of religion and mental health, both in theory and practice. Amazingly, she masters the western and eastern psychological theory, and then constructs them into her own theory which is linked to primary, middle, and high educational level. Practically, she achieves her expertise and skill in psychotherapy and counseling by teaching, writing, preaching, and opening a private counseling practice. Her main source is the fundamental doctrine of religious teachings: prayer, charity, fasting, and pilgrimage in which she thoroughly analyzes by revealing the dimensions of mental health in them. By using descriptive analysis on her books and translated works as primary sources, and applying interview technique with teachers as well as observation technique on cases that exist at Ruhama Islamic Educational Institution, under the auspices of the Prof. Dr. Zakiah Daradjat Foundation Jakarta, some interesting findings are discovered. Scientifically, no one has previously comprehended mental health and psychology of religion before Zakiah. In turn, both disciplines are applied at Colleges for Religious Studies (Perguruan Tinggi Keagamaan- hereinafter called PTK) in the form of an academic supervisory. Initially, it was counseling, but has now evolved into coaching and training. Meanwhile, the implementation of her thought in Ruhama focuses on guidance and counseling. At last, this study shows Zakiah’s thought does not only influence the concept of psychology of religion and mental health, but also affects the practice of counseling in primary, middle to high educational institutions. Penelitian ini menyajikan pemikiran dan peran Prof. Zakiah Daradjat, seorang pemimpin Muslim wanita modern dengan multitalent di Indonesia. Dia adalah seorang ahli dalam psikologi agama dan kesehatan mental, baik dalam teori dan praktek. Hebatnya, dia menguasai teori psikologi Barat dan Timur, dan kemudian membangun ke teori sendiri yang terkait dengan pendidikan dasar, menengah dan tinggi. Secara praktis, ia mencapai keahlian dan keterampilannya dalam psikoterapi dan konseling dengan mengajar, menulis, berkhutbah, dan membuka praktek konseling pribadi. Sumber utamanya adalah doktrin fundamental ajaran agama: doa, amal, puasa, dan haji di mana ia benar-benar menganalisa dengan mengungkapkan dimensi kesehatan mental di dalamnya. Dengan menggunakan analisis deskriptif pada buku-buku dan karya-karya terjemahan sebagai sumber primer, dan menerapkan teknik wawancara dengan guru serta teknik observasi pada kasus yang ada di Lembaga Pendidikan Islam Ruhama, di bawah naungan Prof. Dr. Zakiah Daradjat Yayasan Jakarta, beberapa temuan menarik yang ditemukan. Secara ilmiah, tidak ada seorangpun sebelumnya memahami kesehatan mental dan psikologi agama sebelum Zakiah. Pada gilirannya, kedua disiplin yang diterapkan di Sekolah Tinggi Studi Keagamaan (Perguruan Tinggi Keagamaan- selanjutnya disebut PTK) dalam bentuk pengawasan akademik. Awalnya, itu konseling, tetapi sekarang telah berkembang menjadi pembinaan dan pelatihan. Sementara itu, pelaksanaan pemikirannya di Ruhama berfokus pada bimbingan dan konseling. Akhirnya, penelitian ini menunjukkan pemikiran Zakiah ini tidak hanya mempengaruhi konsep psikologi agama dan kesehatan mental, tetapi juga mempengaruhi praktek konseling di SD, menengah hingga di lembaga pendidikan tinggi.